Entidades dermatológicas y malestar psicológico en pacientes atendidos en un centro dermatológico de la ciudad de Loja - Ludeña Gavilanes, Evelyn Marián (2022)
Dermatological entities are a wide variety of conditions that affect the skin and, if it is not treated correctly can trigger emotions, such as anxiety and depression, and subsequently lead to acts that hinder the personal growth of the patient. Also, there are few studies that focus on the variables present in this research. For this reason, our objective is to determine the dermatological entities and the relationship with psychological ailments in patients treated at a dermatological center in the city of Loja. This study was descriptive, non-experimental, documentary and with a cross-sectional approach. The SCL Symptom Inventory was applied through an interview, with a sample of 50 patients. It was evidenced that all people with dermatological entities presented psychological ailments, the most frequent psychological ailments were: obsessions and compulsions, anxiety and paranoid ideation, relating to the most frequent entities such as acne, followed by patients with psoriasis and keratosis, with a lower percentage: seborrhea, alopecia, pigmentation disorders and seborrhea/alopecia